Nanoscale Titanium Dioxide Particles Modulate Signaling Cascades for Tumor Necrosis Factor-α Release from Macrophages - Sung Bae Kim; Hiroaki Tao (Journal of Health Science, 2011)
Toxicological and biomedical effects of nanoparticles to living subjects should be elucidated before use for safety. To address this point, we attended to proinflammatory cytokine release from macrophage-like RAW 264.7 cells as a measure of the impact of nanoscale particles to living subjects. We explored the specific impacts of TiO2 particles on the signaling cascades for proinflammatory cytokine and tumor necrosis factor-α (TNF-α release using a bioluminescent coculture system and an ELISA assay in the presence of various chemotherapeutic agents or biochemical inhibitors. This evaluation revealed that the proinflammatory cytokine release from the RAW 264.7 cells is synergically enhanced by the mixture of TiO2 particles and interferon-γ (IFN-γ), and TNF-α release is modulated by 40 nm TiO2 particles via a mitgen activated protein kinase (MAPK)/nuclear factor-kappa B (NE-κB) pathway. The TNF-α release is also affected by the agonist of glucocorticoid receptor in both basal and TiO2-particle-activated conditions. The present study evidences that nanoscale TiO2 particles exert a modulator to the initial steps of inflammation, called TNF-α release from RAW 264.7 cells.